Behavior of steel casing composite piles under lateral loading and parameter optimization. (1st October 2020) - Zhou, Wenwei; Gao, Rongxiong; Zhu, Hongping; Wei, Xin; Cao, Qi; Gao, Zeyu
Highlights: Lateral loading tests on SCC piles and RC piles were addressed. The contact force contributed to the transformation of failure mode of the pile. Effect of steel casings on the behaviors of the original RC piles were clarified. The optimum length-to-diameter ratio of steel casing was proposed. Abstract: The piles of channel bridges generally exist in the form of steel casing composite piles (SCC pile, namely, the reinforced concrete pile wrapped by steel casing) owing to construction factors, such as drilling and temporary platforms. To investigate the effect of steel casings on the behaviors of the original reinforced concrete (RC) piles, and to clarify the reasons for this effect, we conducted a lateral loading experiment on three sets of piles. The three sets of piles included a set of RC piles, a set of SCC piles with partially set steel casings, and a set of piles with fully set steel casings. Each set comprised two identical specimens. In addition, to provide a theoretical basis for determining appropriate parameters for steel casings in practice, parameter analysis was conducted by numerical modeling. The results indicated that the contact force between the steel casing and the RC shaft directly caused the transformation of failure mode of the pile. When the length of steel casing was insufficient, the accumulated contact force resulted in great shear force and bending moment in the uncased RC shaft, and the failure mode of the pile would transform from bending to bending-shear failure. The mechanical behaviors and failure modes of SCC piles were significantly affected by the relative position between the steel casing and the equivalent plastic zone of the original RC shaft. Only if the equivalent plastic zone of the original RC shaft was wrapped by the steel casing, the critical state would be governed by the steel casing, and the bearing capacity and toughness of SCC pile would be significantly improved. Moreover, a fitting formula of the optimum length-to-diameter ratio for a steel casing was proposed, and the most unfavorable length-to-diameter ratio was discussed.